Islamic Corporate Governance, Islamicityfinancial Performance Index And Fraudat Islamic Bank - Lidyah, Rika (Jurnal Akuntansi, 2018)
This research empirically tested the factors of fraud occurrence in sharia banks based on fraud triangle theory, which is motivation, opportunity and rationalization must be fulfilled for the occurrence of fraud. This research develops indicators as a proxy of motivation, opportunity and rationalization. Factors tested in this research is the Islamic Corporate Governance to fraud with the Islamicity Financial Performance Index as a mediator in sharia banks 2012-2016.This research using quantitative method with secondary data. Data are obtained from annual reports published by Islamic banks. The test is done by path analysis and processed using SPSS. The result of research shows that Islamic Corporate Governance has no effect to Islamicity Performance Index, Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio (Islamicity Financial Performance Index) influence to Fraud, Islamic Corporate Governance has no effect to Fraud, and Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio (Islamicity Financial Performance Index) does not mediate the influence of Islamic Corporate Governance to Fraud on Islamic Bank or it can be said that there is no mediation. This research shows that factors based on fraud triangle are effective for use in explaining fraud.